2018
DOI: 10.3390/ijerph15051006
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer Incidence Trend in the Hebei Spirit Oil Spill Area, from 1999 to 2014: An Ecological Study

Abstract: The Hebei Spirit oil spill (HSOS) occurred in the Republic of Korea on 7 December 2007. We aimed to describe the cancer incidence trend in Taean County before and after the oil spill. Five major cancers and leukemia were analyzed. Cancer incidence data were obtained from the Korean National Cancer Center. We compared the standardized incidence rates in Taean with those observed nationwide and selected three coastal areas. Joinpoint regression analysis was used to examine the trends in the average annual percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…Choi et al [ 67 ] conducted a cross-sectional study of 63042 participants to evaluate prostate cancer risk in relation to oil spillage in Taean County. They reported elevated incidence rate ratio (IRR = 1.5; 95% CI: 0.8, 2.7) for the high exposed area compared to the low exposed area (IRR= 0.8; 95% CI: 0.5, 1.4).…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al [ 67 ] conducted a cross-sectional study of 63042 participants to evaluate prostate cancer risk in relation to oil spillage in Taean County. They reported elevated incidence rate ratio (IRR = 1.5; 95% CI: 0.8, 2.7) for the high exposed area compared to the low exposed area (IRR= 0.8; 95% CI: 0.5, 1.4).…”
Section: Resultsmentioning
confidence: 99%
“…A study of the cancer incidence trends in Taean County, which was based on Korean Cancer registry data, showed that from 2007 to 2009, the annual incidence rate of prostate cancer appeared to increase at a more rapid rate than the rates reported nationwide and in three other coastal areas of Korea (Taean: 39.3%, 95% CI −25.9 to 161.8; nationwide: 13.5%, 95% CI 11.7 to 15.4; three coastal areas: 15.6%, 95% CI 11.9 to 19.5) 44…”
Section: Findings To Datementioning
confidence: 76%
“…All residents of Taean, including those in this study cohort, have been monitored for morbidity, mortality and cancer incidence44 using data provided by the National Health Information Database (NHID) and Korea National Cancer Incidence Database (KNCID).…”
Section: Cohort Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to an error during production, the legend presented in Figure 2 in the Results section of the published paper [ 1 ] were incorrect. A corrected version of this figure is provided below.…”
mentioning
confidence: 99%